Manajemen Strategi Dalam Menghadapi Persaingan Bisnis Pada Maskapai Garuda Indonesia di Bandara Internasional I Gusti Ngurah Rai Denpasar - Ida Ayu Trisna Wijayanthi; Ni Putu Ani Suanendri (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract. The tourism industry is very important in the country's economy, especially the island of Bali. This is dominated by air routes or airports, namely I Gusti Ngurah Rai International Airport. The existence of an airline or flight plays an important role in visiting trips. One of the biggest airlines "Garuda Indonesia" which brings tourist visits continues to increase. The purpose of this study is to determine the internal and external factors of the Garuda Indonesia Airline and to determine the competitive strategy adopted by the Garuda Indonesia Denpasar airline in order to maintain or increase market share in business competition. The type of data used is qualitative and quantitative (combination), the analysis uses the SWOT analysis method. Methods of data collection through observation, documentation, interviews and distributing questionnaires of 25 respondents consisting of top to middle level management. The data analysis technique used validity and reliability tests which were then processed into the I-E Matrix, SWOT Diagram and Matrix. Based on the results of the research, it shows that the position of the airline Garuda Indonesia Depasar is in cell 1 (one), namely implementing the Growth Strategy and is located in quadrant 1 (one), which is aggressive growth that can support the Growth strategy by increasing market share, namely with alternative strategies. SO, the development and utilization of the strengths and opportunities of the Garuda Indonesia airline Denpasar.